Laser-triggered lightning discharge - Khan, Nasrullah; Mariun, Norman; Aris, Ishak; Yeak, J. (Institute of Physics Publishing, 2002)
Advances in ultrafast optics in recent years have revived a keen interest in laser-induced dielectric breakdown study. While it is widely accepted that femtosecond laser pulses with peak powers reaching gigawatts can propagate over tens of metres under laboratory conditions, the dynamics underlying this highly nonlinear phenomenon is yet not fully understood. Although initial research on laser-triggered lightning was started with infrared lasers, it was found that they are not suitable to initiate lightning. Recent published literature and experimental work favour the use of ultraviolet (UV) laser pulses as the appropriate means for laser-induced lightning discharge. An analytical solution based on Maxwell's equations has been developed for UV filamentation in air, arising from a dynamic oscillating balance between self-focusing, diffraction and plasma defocusing. This model suggests that UV (220-420 nm) 200 ps laser pulses with a peak power of around 50 MW(or 12.5 mJ input energy) and a beam size of 100 μm are the optimal tool to trigger outdoor lightning. The laser beam size remains relatively small (less than 0.3 mm) after a propagation distance of 200 m up into the normally cloudy and damp atmospheric conditions.